Beyond traditional flexibility: The Jurdan sprint table test for the evaluation of pelvis-femur coordination - Astrella, A.; Moreno-Cabañas, P.; Iordanov, D.; Jiménez-Reyes, P.; Mendiguchia, J. (Scandinavian Journal of Medicine & Science in Sports, 2025)
This study aimed to evaluate the reliability and functional relevance of the Jurdan Sprint Table Test (JSTT), a novel tool designed to assess the dynamic interaction between the pelvis and femurs under high-speed movement conditions. Thirty physically active male participants completed the JSTT, which involved a rapid kicking motion while kinematic data were captured with inertial measurement units. Eighteen participants repeated the protocol after 24-48 h for test-retest reliability analysis. Intraclass correlation coefficients (ICC) ranged from moderate to excellent (ICC = 0.77-0.97, 95% CI 0.50-0.98). Significant correlations (n = 30) were found between static anterior pelvic tilt (APT) and contralateral thigh elevation (r = 0.408, p = 0.025), and between static APT and sagittal pelvic motion (r = 0.517, p = 0.003), indicating that individuals with greater static APT tended to exhibit higher contralateral thigh elevation and greater sagittal pelvic motion during the test. Moreover, contralateral thigh elevation was negatively correlated with total thigh range of motion (ROM) (r = -0.534, p = 0.002). These findings indicate that the JSTT appears to be a reliable method for assessing intersegmental coordination and suggest potential applications in sport performance and rehabilitation screening.